Wind tunnel experimental study on droplet drift reduction by a conical electrostatic nozzle for pesticide spraying - Wei, Zhang; Yongrui, Hou; Xin, Liu; Qi, Lian; Xiaoming, Fu; Bo, Zhang; Haiyang, Wang; Yingqian, Wang (International Journal of Agricultural and Biological Engineering, 2017)
Abstract: Droplet drift wastes pesticide, pollutes the environment, and has become one of the focus issues of agricultural crop protection. Electrostatic spray technology reduces drift to a certain degree. In order to investigate the droplet drift pattern of a conical electrostatic nozzle, the droplet drift mass center distance was defined as an experimental index and used to conduct experimental wind tunnel studies on droplet drift. A mathematical model of the droplet drift mass center distance versus electrostatic voltage and wind speed was created via the regression method. The test results showed that the electrostatic voltage had an insignificant effect on droplet drift, the wind speed and its interaction with the electrostatic voltage had significant effects on droplet drift. When the wind speed was less than 3 m/s and stable, the crop adsorbability of a droplet had a dominant effect on the droplet drift; the droplet drift decreased with the increase of electrostatic voltage. When the wind speed exceeded 3 m/s and was stable, the reduced droplet particle size had a dominant effect on droplet drift, where droplet drift increased as the electrostatic voltage increased. When the wind speed was 0 m/s and the electrostatic voltage was 12 kV, the minimum droplet drift mass center distance was 35.5 mm, which was 56 mm less than that of conventional nozzle droplet drift. Therefore, a conical electrostatic nozzle is inapplicable for operation in an environment where wind speeds exceed 3 m/s. This study provides a reference for optimizing operational parameters of conical electrostatic nozzles and improving the anti-drift capability of droplets.Keywords: pesticide spraying, conical electrostatic nozzle, droplet drift, wind tunnel, experimental study, electrostatic sprayerDOI: 10.3965/j.ijabe.20171003.3074Citation: Zhang W, Hou Y R, Liu X, Lian Q, Fu X M, Zhang B, et al. Wind tunnel experimental study on droplet drift reduction by a conical electrostatic nozzle for pesticide spraying. Int J Agric & Biol Eng, 2017; 10(3): 87–94.